Devoir participer quand on est déjà (involontairement) impliqué : le cas des parents en protection de l’enfance - Claire de Saint Martin; Gilles Monceau (Sociétés et Jeunesses en Difficulté)
Involving parents in child protection has been a public policy injunction since the early 2000s. However, this participation is not self-evident and raises questions for the services concerned. In 2019, a child protection association commissioned action research on this issue as part of the process of rewriting its project. The research involved six researchers working with the association’s various stakeholders: professionals, parents and young people. This article focuses on parent participation, based on interviews with some of them and a collective analysis of professional systems and situations carried out with professionals from several of the association’s departments. The results of this institutional socio-clinical research show that the involvement of parents, involuntary when they are under court supervision, does not necessarily lead to their participation. Their infantilisation by professionals, the contradictions between the trust they place in the professionals who work with them and the distrust they express towards the services, and the tension between the reality of these services and that daily experienced by parents are all obstacles to their effective participation. However, the parents are not fundamentally opposed to the services, and their comments reveal a capacity for analysis and contextualisation that could provide a basis for action.